MAKING SMILES-SAME OR DIFFERENT PERSPECTIVE FOR PROSTHODONTIST AND ORTHOTONTIST? - Dana Gabriela Budală; Monica Mihaela Scutariu; Zenaida Surlari; Corina Ciupilan; Cristian Romanec; Dragoș Ioan Virvescu (Romanian Society of Oral Rehabilitation, 2022)
Dental professionals are compelled to perform high-quality dental restorations because of the indisputable benefits of a beautiful smile.The esthetic planning of the smile is subjective in the sense that the clinician must be aware of the most significant factors in order to undertake treatments with a predictable outcome